A Comparative Study of the Number of Iqamah in Hadith: Sunni and Shia Perspectives - Zahri, Ahmad Fauzan; Afifah, Alvin; Said, Imam Ghazali; Khoshyatulloh, Arfedin Hamas (Ishlah: Jurnal Ilmu Ushuluddin, Adab dan Dakwah, 2024)
This study discusses the number of iqamah phrases contained in the Sunni and Shia perspectives. Iqamah has a purpose as a marker in the implementation of prayer to prepare and close the safes. In practice, there are different variations in the number of numbers in the iqamah sentences. This difference occurs between the Sunni and Shia schools of thought because both have different hadith sources as references in the implementation of the iqamah. The research method used is descriptive comparative with the type of research applied is library research. The main sources of literature in this study are Kutub al-Tis‘ah, Uṣūl al-Kāfī and Furū' al-Kāfī. The results show that there are differences in the tradition of iqamah between the two schools of thought. Iqamah has different origins in the Sunni and Shia schools. According to the Sunnis, the iqamah originated from the dream of ‘Abdullāh ibn Zayd which was later confirmed by the Prophet, and the Shias believe that the iqamah is a revelation delivered from the Angel Gabriel. Then in terms of the number of iqamah numbers, Sunnis have three different variations of the number of iqamah, namely the opinion that says 17 sentences, 11 sentences, and 10 sentences. While the Shia argue that the iqamah has 17 sentences, but the content is different from the Sunni school and there is an additional sentence of Ḥayya ‘Alā Khair al-‘Amal which is different from Sunni. Abstrak. Penelitian ini membahas mengenai jumlah bilangan frasa iqamah yang terdapat dalam hadis perspektif Sunni dan Syiah. Iqamah memiliki tujuan sebagai penanda dalam pelaksanaan shalat untuk mempersiapkan dan merapatkan shaf. Pada praktiknya, terdapat perbedaan variasi jumlah bilangan dalam kalimat-kalimat iqamah. Perbedaan ini terjadi di antara mazhab Sunni dan Syiah dikarenakan keduanya memiliki sumber hadis yang berbeda sebagai rujukan dalam pelaksanaan iqamah. Metode penelitian yang digunakan adalah deskriptif komparatif dengan jenis penelitian yang diterapkan adalah riset kepustakaan (library research). Sumber literatur utama dalam penelitian ini adalah Kutub al-Tis‘ah, Uṣūl al-Kāfī dan Furū‘ al-Kāfī. Hasil penelitian menunjukkan bahwa adanya perbedaan tradisi iqamah di antara dua mazhab tersebut. Iqamah mempunyai asal-usul yang berbeda di mazhab Sunni dan Syiah. Menurut Sunni, iqamah berasal dari mimpi ‘Abdullāh ibn Zaid yang kemudian dibenarkan oleh Nabi saw., dan Syiah meyakini bawah iqamah adalah wahyu yang disampaikan dari Malaikat Jibril. Kemudian dari segi jumlah bilangan iqamah, Sunni memiliki 3 variasi jumlah iqamah yang berbeda, yaitu pendapat yang mengatakan 17 kalimat, 11 kalimat, dan 10 kalimat. Sedangkan Syiah berpendapat bahwa iqamah memiliki 17 kalimat, namun isinya berbeda dengan mazhab Sunni dan terdapat tambahan kalimat Ḥayya ‘Alā Khair al-‘Amal yang berbeda dengan Sunni.